Struggling readers CAN succeed : targeted solutions based on complex views of real kids in classrooms and communities - Nilsson, Nina; Gandy, Sandra E. (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2013)
In spite of No Child Left Behind and the support provided by Response To Intervention, significant numbers of students continue to struggle with literacy. This text addresses learning-related needs of individual students in addition to interventions for the challenges they face. Struggling readers represent many different ethnicities, socio-economic levels, languages, and dialects in any combination and possess an even wider variety of social, cultural, motivational, literacy, and real world experiences. Through the presentation of case studies, this book considers these factors and their influence on literacy development and suggests ways to adapt research-based instructional strategies and approaches, as well as classroom practices to address them. It also includes related recommended resources. The text appeals to the concerns of classroom teachers, reading specialists, and faculty in teacher education programs, as well as anyone looking for practical, research-based ways to further the literacy development of individuals who struggle to read.
Keywords: Reading -- Remedial teaching -- United States -- Case studies.; Language arts -- Social aspects -- United States -- Case studies.; Individualized instruction -- United States -- Case studies.; elektronické knihy; Case studies.; Education -- Teaching -- Subjects -- Language Arts.; Literacy.; Teaching of reading, writing and numeracy.; Educational: Language, literature and literacy.; electronic books